The Factors Affecting Audit Quality - Tigor Sitorus; Tonny Hendratono; Nesia Fransisca (Universitas Hayam Wuruk Perbanas, 2020)
This study aims to extend and investigate the relationship between professionalism, implementation of professional ethics, and audit quality by proposing client acceptability as a mediating variable for filling the previous research gap. It is a quantitative method conducted at public accountant offices in Jakarta with 176 respondents from 41 offices. The data were analyzed using the Structural Equation Model. The model is good and the Confirmatory Factor Analysis proves to have a high loading. The results show that professionalism has an insignificant negative effect on audit quality, but it has a significant negative effect on client acceptability. The implementation of professional ethics has a significant positive effect on audit quality and client acceptability. The client acceptability has a significant positive effect on audit quality. The result proves that client acceptance mediates the effect of implementing professional ethics on audit quality. The implication of this study is to contribute to the public accounting firm in a low-risk client acceptance policy in providing information so that public accountants can avoid submitting misleading financial information.